2018
DOI: 10.1002/ecy.2538
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical multi‐population viability analysis

Abstract: Population viability analysis (PVA) uses concepts from theoretical ecology to provide a powerful tool for quantitative estimates of population dynamics and extinction risks. However, conventional statistical PVA requires long‐term data from every population of interest, whereas many species of concern exist in multiple isolated populations that are only monitored occasionally. We present a hierarchical multi‐population viability analysis model that increases inference power from sparse data by sharing informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 56 publications
(92 reference statements)
1
51
0
Order By: Relevance
“…We identified exceptions to these Conservation Biology Volume 34, No. 2, 2020 Leasure et al (2018). general rules, either due to variable environmental conditions or stochasticity ignored in simple habitat extent thresholds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified exceptions to these Conservation Biology Volume 34, No. 2, 2020 Leasure et al (2018). general rules, either due to variable environmental conditions or stochasticity ignored in simple habitat extent thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…Higher peak flows had a weak positive effect on population growth rates (Leasure et al 2018). Riparian vegetation was assessed by the satellite-based normalized difference vegetation index (NDVI) (Pettorelli et al 2011) calculated from Landsat images with the Google Earth engine (Gorelick et al 2017); NDVI does not detectably effect LCT carrying capacities (Leasure et al 2018).…”
Section: Mpva Model Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…They allow for the identification of the most important spatial parameters that influence extinction. For example, in population viability analysis (PVA), remote sensing can be used to assess different environmental indicators that affect the existence of a given population in a certain area (Leasure et al 2019; Loannidou and O’Hanley 2019; Roberts et al 2016). GIS techniques also allow for the identification of which habitat patches have the greatest effect on metapopulation viability and to run extinction simulations under various model conditions (McCusker et al 2017) of executed analysis based on historical data to identified parameters that may affect fish extinction in the present (Klippel et al 2016; Tedesco et al 2005).…”
Section: Introductionmentioning
confidence: 99%